Introduction to probability / Nur Idayu Alimon ... [et al.] - Alimon, Nur Idayu; Tukiman, Norbaiti; Ahmad, Nur Intan Syafinaz; Johari, Norzarina; Mohamad Yunos, Nurhazirah (College Of Computing, Informatics And Mathematics Universiti Teknologi Mara Cawangan Johor, Pasir Gudang Campus, 2024)
This e-book consists of five sections which starts with introduction. In Introduction section, some definitions are stated to give an information to the students. The next sections that follow are set theory, rules of probability, counting rule, and tree diagram and Bayes’ theorem. In each section, some examples and exercises are given to give the students better understanding.